Measuring vaccination willingness in response to COVID-19 using a multi-criteria-decision making method - Adnan Sarwar; Naima Nazar; Nimra Nazar; Alia Qadir (Taylor & Francis Group, 2021)
The pandemic COVID-19 is continued to the massive burden of morbidity and mortality while disrupting economies and societies all over the world. At an earlier stage, wearing a face mask, social distancing, and hand hygiene were suggested to limit the transmission of this infection. The WHO, CDC, and other governing bodies were doing an effort to develop the coronavirus vaccine. Now COVID-19 vaccines are available to protect people against the coronavirus. People are hesitant about whether to receive a vaccination or do not to vaccinate. This study was aimed to analyze the COVID-19 vaccination willingness level of the general public of Pakistan to manage the COVID-19 disease. A multi-criteria decision-making method known as an analytical hierarchical method was applied to determine the COVID-19 vaccination willingness level of the public. The significant determinants of COVID-19 vaccination willingness were cues to action, perceived benefits, positive attitude, government recommendation, as well as perceived stress scoring high weights to the vaccination. Determinants of willingness to uptake the COVID-19 vaccine were individual decision, vaccine origin, adapting to change, and perceived barriers high obstacles to vaccinating. The determinants relating to the COVID-19 vaccine may help to increase the uptake of the vaccination program. The government may need communication campaigns to reinforce the benefits of the vaccine.